Contractors' strategies in joint venture during economic growth and economic downturn - Abdul Aziz, Nur 'Izzati; Hasan, Sharina Farihah (2015)
The Malaysian economy nowadays registers positive growth ever since the global recession occurred in 2008-2009 and since then, more construction projects were proposed by the government in order to facilitate the needs of the nation. Along with the rapid growth in construction technology, joint venture can be seen as an option for contractors to share their resources and risks with other contractors. This paper aims to report on a study on the contractors’ strategies in joint venture for construction works during economic growth and economic downturn. Through desk study, it was found that the strategies include cost control, partner selection, marketing, etc. Consequently, questionnaire survey was conducted to validate the initial findings. The paper concludes that not all of the strategies highlighted in literatures are significant to be considered during the time when the economy is registering positive and negative economic growth.